ВОСПИТАНИЕ ПАТРИОТИЗМА ЧЕРЕЗ НАУЧНО-ИССЛЕДОВАТЕЛЬСКИЙ ПОДХОД В ОБУЧЕНИИ ИСТОРИИ - Ковальчук, Н.В. (My University, 2019)
Аннотация В настоящей статье освещены вопросы патриотизма как фундамента успеха нашего многонационального и многоконфессионального общества. Как вещает глава Республики Казахстан в своем недавнем послании: «Необходимо воспитывать в себе и наших детях это высокое гражданское качество, научить гордиться страной и ее достижениями, привить чув- ство глубокого понимания единства судеб и возможностей процветания всех людей, прожи- вающих на территории республики». Исходя из этого главная обязанность учителя истории – познакомить учащихся со всей исторической правдой, раскрыть главные достижения миро- вой культуры, критически рассматривая прошлое. Abstract This article highlights the issues of patriotism as the Foundation of the success of our multi- ethnic and multi-religious society. As the head of the Republic of Kazakhstan broadcasts in his recent address: «It is necessary to educate ourselves and our children this high civic quality, to teach them to be proud of the country and its achievements, to instill a sense of deep understanding of the unity of destinies and opportunities for prosperity of all people living on the territory of the Re- public». Based on this, the main duty of the teacher of history – to acquaint students with all the historical truth, to reveal the main achievements of world culture, critically examining the past.
Fostering patriotism through research approach in training of history
Keywords: патриотизм; история; научно-исследовательская деятельность школьников.; patriotism; history; pupil’s research activity